Yield spreads on EMU government bonds: How the financial crisis has helped investors to rediscover risk - Catharina Klepsch; Timo Wollmershäuser (Intereconomics, 2011)
The creation of a single currency is deemed to produce further heterogeneity in regional trade, as regions differ in their exposure to trade with other European countries. It is possible to disentangle two separate effects on bilateral trade, namely the 'exchange rate volatility effect' (from exchange rate fixing in 1999) and the pure 'common currency effect' (resulting from the issuing of a new currency in 2002). This paper presents an empirical analysis that shows evidence of a regional concentration of currency union effects in a few Spanish regions.
Keywords: 330